Trade union responses to precarization :|the case of mandatory alternative dispute resolution in Turkey - Yüzüak, Batuğhan. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2021., 2021)
The world of work has gradually fallen under the influence of the precarization trend, especially since the 1980s. One of the domains that this trend that can be observed is the changes in the judicial system and labor litigation. Trade union perceptions in the context of dual labor markets provide a valuable gateway into the implications of these changes for workers‟ rights and employment security. Turkey introduced a voluntary form of alternative dispute resolution (ADR) for individual labor disputes in 2012, which the country then made compulsory in 2018. In the current practice, ADR in individual labor disputes is a prerequisite for litigation. In the context of a low rate of unionization and collective bargaining coverage, trade union confederations in Turkey are organized along political lines. This thesis examines trade union responses to the introduction of alternative dispute resolution for individual labor disputes. In doing so, the thesis also investigates how their responses have changed over the course of three phases: the introduction of voluntary ADR, the transition from voluntary to mandatory ADR, and the implementation of mandatory ADR. This thesis is an exploratory, qualitative study that relies on six in-depth interviews and five written interviews with respondents from the three largest confederations and seven trade unions affiliated with these confederations. Based on a thematic analysis, the thesis finds that even though the initial responses of trade unions differ from each other in the first two phases, they have reached a consensus in the third phase against the use of mandatory ADR in individual labor disputes. The thesis argues that this consensus is especially noteworthy given the political divisions between these unions. This thesis demonstrates that confederations and trade unions object to the practice of mandatory ADR because, they see this practice, compared to labor litigation, has led to the erosion of the rights and employment security of non unionized workers especially. While this common response might lead to a momentum for trade union revitalization, the restrictive political atmosphere and the labor regime seem to restrict such possibility.
Keywords: Dispute resolution (Law); Labor unions.